2014
DOI: 10.1039/c4tb00643g
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-effective photothermal therapy for prostate cancer cells using dual aptamer-modified gold nanostars

Abstract: A novel general platform for disease-specific photothermal therapy. This is the first demonstration of gold nanostars with tremendous efficiency and impressive selectivity for the targeted cancer, particularly the simultaneous targeting of PSMA(+) and PSMA(−) prostate cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…Dark-fi eld microscopy showed that the biocompatible gold nanoparticles were easily internalized and most of them localized within the cells. Jo et al performed the PEGylation of GNS synthesized by seed growth with bifunctional O -[2-(3-mercaptopropionylamino)ethyl]-O ′-methylpolyethylene glycol [ 60 ]. These PEGylated gold nanostars were further conjugated with aptamers for the targeting of prostate cancer cells.…”
Section: Pegylation Of Gnsmentioning
confidence: 98%
See 1 more Smart Citation
“…Dark-fi eld microscopy showed that the biocompatible gold nanoparticles were easily internalized and most of them localized within the cells. Jo et al performed the PEGylation of GNS synthesized by seed growth with bifunctional O -[2-(3-mercaptopropionylamino)ethyl]-O ′-methylpolyethylene glycol [ 60 ]. These PEGylated gold nanostars were further conjugated with aptamers for the targeting of prostate cancer cells.…”
Section: Pegylation Of Gnsmentioning
confidence: 98%
“…Novel valuable therapeutic complexes, namely dual-aptamermodifi ed gold nanostars, for the targeting of prostate cancers have been developed recently [ 60 ]. The aptamers were conjugated to PEGylated GNS via disulfi de bonds.…”
Section: Other Examples Of Functionalization Of Gnsmentioning
confidence: 99%
“…Jo et al developed novel valuable therapeutic complexes, namely dual-aptamermodifi ed GNS, for the targeting of prostate cancers, including PSMA(+) and PSMA(−) cells [ 46 ]. The synthesized probes were subsequently analyzed for cytotoxicity tests, cell uptake, and in vitro photothermal therapy.…”
Section: Application Of Gns For Thermal Therapymentioning
confidence: 99%
“…CTAB-free, biocompatible, single-crystalline nanoprisms have been reported, [ 142 ] as well as their application to in vivo photothermal cell ablation of Hydra vulgaris. [ 146 ] Dual aptamer-modifi ed Au NSs presented high selectivity toward prostate cancer cells, through accumulation in PSMA(+) and PSMA(-) cells, and highly effi cient therapy was achieved using an 808 nm laser under an irradiance of 0.3 W cm −2 , which is below the permitted value for skin exposure (0.329 W cm −2 ). Recent interest has been directed toward nanoparticle morphologies containing sharp edges and tips, as these have been demonstrated to display highly active LSPRs, [ 144 ] which are favorable for heat generation, meaning that so-called Au nanostars (Au NSs) are also suitable candidates as nanoheaters.…”
Section: Progress Reportmentioning
confidence: 99%